Pyrolysis of Table Sugar. (2nd October 2013) - Bulut, Adnan; Karagöz, Selhan
Abstract : Table sugars were pyrolyzed at different temperatures (300, 400, and 500°C) in a fixed-bed reactor. The effect of pyrolysis temperature on yields of liquid, solid, and gaseous products was investigated. As expected the yield of liquid products gradually increased and the yield of solid products gradually decreased when the pyrolysis temperature was raised. The yield of liquid products was greatest (52 wt%) at 500°C. The composition of bio-oils extracted with diethyl ether was identified by means of gas chromatography mass spectrometry (GC-MS), nuclear magnetic resonance ( 1 H-NMR), and Fourier transform infrared spectroscopy (FTIR). The following compounds were observed in bio-oils produced from the pyrolysis of table sugar at 500°C: 1, 4:3, 6-dianhydro- α -d-glucopyranose, 5-(hydroxymethyl) furfural, 5-acetoxymethyl-2-furaldehyde, and cyclotetradecane liquid product. The relative concentration of 5-(hydroxymethyl) furfural was the highest in bio-oils obtained from pyrolysis of table sugars at 500°C.